Negotiating the Role of Mother and Child's Right in a Feminist Perspective: Analysis of the Film Ali dan Ratu Ratu Queens (2021) - Itsna Syahadatud Dinurriyah (Journal of Feminism and Gender Studies, 2026)
This research explores the negotiation of a mother’s role and a child’s rights through a feminist lens in the Indonesian film Ali dan Ratu Ratu Queens (2021), directed by Lucky Kuswandi. The study aims to examine how motherhood is portrayed in the context of migration, personal ambition, and maternal absence, and how these portrayals intersect with the child’s right to love, care, and identity. By employing feminist film theory and narrative analysis, the research interrogates the tension between female autonomy and maternal responsibility. The character of Mia (Marissa Anita), a mother who leaves her son to pursue a career abroad, becomes a focal point in analyzing how the film presents alternative models of womanhood that diverge from traditional expectations. Simultaneously, the character of Ali (Iqbal Ramadhan), the abandoned son, offers insight into the emotional and psychological struggles a child faces in the absence of a parent. This study reveals how the film problematizes the idealization of motherhood and advocates for a more inclusive understanding of women’s choices and children’s needs. The findings suggest that Ali dan Ratu Ratu Queens provides a critical reflection on gender, care, and intergenerational negotiation within feminist discourse in contemporary Indonesian cinema.